Nano-composite hydrogel of double-load eye protection factor as well as preparation method and application of nano-composite hydrogel

By designing a nanocomposite hydrogel with double load eye protection factors, the problem of synergistic efficacy and low bioavailability of anthocyanins and lutein in the complex is solved, and the stability and delivery of these two biologically active compounds are achieved. The improvement of performance provides a novel technical solution for the development of eye protection gel gummy.

CN119488126APending Publication Date: 2025-02-21SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411503748.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Due to environmental instability and different physical and chemical characteristics, anthocyanins and lutein are difficult to achieve synergistic efficacy and high bioavailability when simply recombined, and there is a lack of an effective delivery system.

Method used

A nanocomposite hydrogel with double-load eye protection factor was designed to form nanosized in gluconolactone through lutein-loaded zein nanoparticles, anthocyanins, caseinates, and arabinoxicans. Composite material realizes co-loading and delivery of anthocyanins and lutein.

Benefits of technology

It significantly improves the environmental stability and bioavailability of anthocyanins and lutein, achieves a better release effect, and provides new ideas for the preparation of eye protection gel gum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103238210000021
    Figure BDA0005103238210000021
  • Figure BDA0005103238210000061
    Figure BDA0005103238210000061
  • Figure BDA0005103238210000062
    Figure BDA0005103238210000062
Patent Text Reader

Abstract

The invention provides nano-composite hydrogel with double-load eye protection factors as well as a preparation method and application of the nano-composite hydrogel. Specifically, the invention provides a nano-composite hydrogel, which comprises zein nanoparticles loaded with xanthophyll, and zein nanoparticles loaded with xanthophyll, the raw materials comprise anthocyanin, caseinate and arabinoxylan; a glucolactone; and water. The nano-composite hydrogel disclosed by the invention can be used for simultaneously embedding, protecting and delivering the xanthophyll and the anthocyanin, and is very suitable for preparing functional foods for relieving asthenopia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of food chemistry and functional food, and in particular to a nano composite hydrogel with double loading of eye protection factors and a preparation method and application thereof. Background Art

[0002] Vision problems are becoming a global concern, especially in the digital age, where people are becoming more and more dependent on electronic devices, leading to widespread problems of visual fatigue and decreased vision. Anthocyanins are powerful natural antioxidants that help relieve visual fatigue caused by oxidative stress, promote the regeneration of rhodopsin on the retina, and increase retinal enzyme activity. Lutein has the ability to filter blue light, prevent macular degeneration, and reduce light-induced oxidative damage to retinal pigment epithelial cells and chemical-induced oxidative apoptosis of photoreceptor cells. In addition, some previous studies have also found that the combination of anthocyanins and lutein is better than that of a single ingredient. However, due to the environmental instability and different physicochemical properties of anthocyanins and lutein, such as anthocyanins are hydrophilic and lutein are hydrophobic, simply combining anthocyanins and lutein may greatly limit their synergistic efficacy and bioavailability.

[0003] Therefore, it is necessary to design and prepare a delivery system that can simultaneously encapsulate, protect and deliver these two bioactive compounds, so as to further promote their application in eye-protecting functional foods. So far, no relevant research has reported on the delivery system for co-encapsulation and delivery of anthocyanins and lutein. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a nano composite hydrogel capable of simultaneously embedding, protecting and delivering double-loaded eye protection factors of lutein and anthocyanin.

[0005] In a first aspect, the present invention provides a nanocomposite hydrogel, comprising:

[0006] zein nanoparticles loaded with lutein;

[0007] anthocyanins, caseinates, arabinoxylans;

[0008] Gluconolactone; and

[0009] water.

[0010] In another preferred embodiment, a mixture of zein nanoparticles loaded with lutein, anthocyanins, caseinate, arabinoxylan and water is acidified with gluconolactone to form the nanocomposite material.

[0011] In another preferred embodiment, the arabinoxylan has a structure shown in Formula I:

[0012]

[0013] In another preferred embodiment, the molecular weight of the arabinoxylan is 100,000-130,000 Da, such as 110,000 Da or 120,000 Da.

[0014] In another preferred embodiment, the nanocomposite hydrogel comprises:

[0015] 0.05-1 parts by weight, preferably 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or 0.8 parts by weight of zein nanoparticles loaded with lutein;

[0016] 15-30 parts by weight of anthocyanins, preferably 16, 18, 20, 22, 24, 26 or 28 parts by weight;

[0017] 40-70 parts by weight of casein, preferably 45, 50, 55, 60, 65 or 68 parts by weight;

[0018] 5-20 parts by weight of arabinoxylan, preferably 8, 10, 12 or 15 parts by weight;

[0019] 2-8 parts by weight, preferably 4, 5, 6 or 7 parts by weight of gluconolactone; and

[0020] Water: 700-950 parts by weight, preferably 800, 850, 880, 900, 920 or 940 parts by weight.

[0021] In another preferred embodiment, the nanocomposite hydrogel comprises 0.001-0.02 parts by weight of lutein, preferably 0.002, 0.004, 0.006, 0.008, 0.01, 0.012, 0.015 or 0.018 parts by weight.

[0022] In another preferred embodiment, the nanocomposite hydrogel comprises one or more characteristics selected from the following group:

[0023] Zein nanoparticles loaded with lutein 0.05-1 g / L, preferably 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or 0.8 g / L;

[0024] Anthocyanins 15-30 g / L, preferably 16, 18, 20, 22, 24, 26 or 28 g / L;

[0025] Casein 40-70 g / L, preferably 45, 50, 55, 60, 65 or 68 g / L;

[0026] Arabinoxylan 5-20 g / L, preferably 8, 10, 12 or 15 g / L; and / or

[0027] Gluconolactone 2-8 g / L, preferably 4, 5, 6 or 7 g / L.

[0028] In another preferred embodiment, the nanocomposite hydrogel contains 0.001-0.02 g / L lutein, preferably 0.002, 0.004, 0.006, 0.008, 0.01, 0.012, 0.015 or 0.018 g / L.

[0029] In another preferred embodiment, in the nanocomposite hydrogel, the water content is 700-950 g / L, preferably 800, 850, 880, 900, 920 or 940 g / L.

[0030] In another preferred embodiment, the lutein-loaded zein nanoparticles account for 0.05-1wt%, preferably 0.01-0.3wt%, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06 or 0.08wt% of the nanocomposite material.

[0031] In another preferred embodiment, the weight ratio of lutein to zein is 1:25-120, preferably 1:50-100, such as 1:40, 1:50, 1:55, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110 or 1:120.

[0032] In another preferred embodiment, the dehydrated particle size of the zein nanoparticles loaded with lutein is 30-55 nm, preferably 35-50 nm; the particles are usually spherical.

[0033] In another preferred embodiment, the hydrated particle size of the zein nanoparticles loaded with lutein is 60-100 nm, preferably 65-85 nm.

[0034] In another preferred embodiment, the ratio of anthocyanidin to caseinate is 1:1.5-4, preferably 1:2-3.

[0035] In another preferred embodiment, the caseinate is selected from the group consisting of sodium caseinate, calcium caseinate, and magnesium caseinate.

[0036] In another preferred embodiment, the mass ratio of arabinoxylan to caseinate is 1:2-8, preferably 1:3-6, and more preferably 1:4-5.

[0037] In another preferred embodiment, the usage ratio of gluconolactone to caseinate is 1:2-20, preferably 1:5-15, such as 1:6, 1:8, 1:10 or 1:12.

[0038] In another preferred embodiment, the water content in the nanocomposite hydrogel is 70-95 w / w%, preferably 80-90 w / w%, such as 75%, 85%, 88%, 90% or 92%.

[0039] In another preferred embodiment, the nanocomposite hydrogel is a hydrogel in which nanoparticles are dispersed.

[0040] The second aspect of the present invention provides a method for preparing the nanocomposite hydrogel according to the first aspect of the present invention, comprising the steps of:

[0041] (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein;

[0042] (ii) adding the alcohol solution dropwise into water and removing the residual alcohol to obtain or adjust the concentration to obtain an aqueous solution I of zein nanoparticles loaded with lutein;

[0043] (iii) providing an aqueous solution II comprising anthocyanidins, caseinate and arabinoxylan;

[0044] (iv) mixing the aqueous solution I with the aqueous solution II, and adding gluconolactone to form a gel, thereby obtaining the nanocomposite hydrogel.

[0045] In another preferred embodiment, the gelling temperature in step (iv) is 20°C-40°C, preferably 30±5°C.

[0046] In another preferred embodiment, the gelling time in step (iv) is 3h-5h, preferably 3.5-4.5h.

[0047] The third aspect of the present invention provides a soft candy, comprising:

[0048] zein nanoparticles loaded with lutein;

[0049] anthocyanins, caseinates, arabinoxylans;

[0050] Additional gelling agents;

[0051] Gluconolactone; and

[0052] water.

[0053] In another preferred embodiment, the additional gelling agent is selected from the group consisting of gelatin, alginate, pectin, cellulose derivatives, starch and derivatives thereof.

[0054] In another preferred embodiment, the additional gelling agent is 1-20 w / v%, preferably 5-15 w / v%, such as 2%, 4%, 5%, 6%, 8%, 10%, 12%, 15%, 16% or 18% of the soft candy.

[0055] In another preferred embodiment, the soft candy further comprises: preservatives, pigments, flavoring agents, spices, or a combination thereof.

[0056] The fourth aspect of the present invention provides a method for preparing the soft candy as described in the fourth aspect of the present invention, comprising the steps of:

[0057] (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein;

[0058] (ii) adding the alcohol solution dropwise into water and removing the residual alcohol to obtain or adjust the concentration to obtain an aqueous solution I of zein nanoparticles loaded with lutein;

[0059] (iii) providing an aqueous solution II-a comprising anthocyanidins, caseinate, arabinoxylan and the additional gelling agent;

[0060] (iv) mixing the aqueous solution I with the aqueous solution II-a, and adding gluconolactone to form a gel, thereby obtaining the soft candy.

[0061] Preferably, the gelling temperature in step (iv) is 20°C-40°C, preferably 30±5°C.

[0062] Preferably, the gelling time in step (iv) is 3 h to 5 h, preferably 3.5 to 4.5 h.

[0063] The fifth aspect of the present invention provides the use of the nanocomposite hydrogel as described in the first aspect of the present invention or the soft candy as described in the third aspect of the present invention in the preparation of a functional food for relieving visual fatigue.

[0064] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 (a) Digital photos of blank NPs and Lu-NPs; (b) Encapsulation efficiency and loading capacity of Lu-NPs;

[0066] Figure 2Particle size and polydispersity index of blank NPs and Lu-NPs (a); Potential (b) test results;

[0067] Figure 3 SEM images and particle size distribution of blank NPs and Lu-NPs;

[0068] Figure 4 Fluorescence spectra of blank NPs and Lu-NPs at 298K (a), 303K (b), and 313K (c);

[0069] Figure 5 IR spectra of lutein, zein, physical mixture of lutein and zein nanoparticles, blankNPs, and Lu-NPs;

[0070] Figure 6 X-ray diffraction patterns of lutein, physical mixture of lutein and zein nanoparticles, blank NPs, and Lu-NPs;

[0071] Figure 7 Digital photos of ACN-gel and Lu-NPs / ACN-gel;

[0072] Figure 8 SEM (a) and XRM (b) images of ACN-gel and Lu-NPs / ACN-gel;

[0073] Fig. 9 IR spectra of ACN-gel and Lu-NPs / ACN-gel;

[0074] Fig.10 Rheological test results of ACN-gel and Lu-NPs / ACN-gel: apparent viscosity (a); frequency sweep (b);

[0075] Fig.11 Photostability (a) and thermal stability (b) of free anthocyanins and anthocyanins loaded in ACN-gel and Lu-NPs / ACN-gel; Photostability (c) and thermal stability (d) of free lutein and lutein loaded in Lu-NPs and Lu-NPs / ACN-gel;

[0076] Fig.12 In vitro release curves of ACN (a) and Lu (b) from ACN-gel, Lu-NPs, and Lu-NPs / ACN-gel.

[0077] Fig.13 Digital photo of the nanocomposite hydrogel after adding gelatin (a); schematic diagram of the gel candy (b). DETAILED DESCRIPTION

[0078] After extensive and in-depth research, the inventors have provided a nanocomposite hydrogel co-loaded with anthocyanins and lutein through a large number of screenings and tests. The composite hydrogel is used as a delivery carrier for the hydrophilic active substance anthocyanins, and the zein nanoparticles are used as a delivery carrier for the hydrophobic active substance lutein. The two systems are combined to prepare a nanocomposite hydrogel, so as to achieve the co-loading and delivery of the dual eye protection components, and at the same time, a better protective effect is exerted on both anthocyanins and lutein, the stability of both is improved, and a better release effect is shown in in vitro release. In addition, the nanocomposite glue is used as a component of the gelling agent to prepare eye protection gel candy, which provides a new idea for snack-based health care. The present invention was completed on this basis.

[0079] the term

[0080] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0081] As used herein, when used in reference to a specific recited numerical value, the term "about" means that the value may vary by no more than 1% from the recited value. For example, as used herein, the expression "about 100" includes all values ​​between 99 and 101 (e.g., 99.1, 99.2, 99.3, 99.4, etc.).

[0082] As used herein, the term "comprising" or "including (comprising)" may be open, semi-closed and closed. In other words, the term also includes "consisting essentially of" or "consisting of".

[0083] As used herein, the term "room temperature" or "normal temperature" refers to a temperature of 4-40°C, preferably, 25±5°C.

[0084] Active ingredients

[0085] The active ingredients of the present invention include anthocyanidins and lutein, including pharmaceutically acceptable salts thereof.

[0086]

[0087] The anthocyanidin may be chlorinated anthocyanidin.

[0088]

[0089] Common pharmaceutically acceptable salts may be sodium salts, potassium salts, or calcium salts.

[0090] The active ingredients of the present invention can be artificially synthesized or extracted from plants (such as blueberry, bilberry, etc.).

[0091] Anthocyanidins and lutein are both important active ingredients for relieving visual fatigue, but both are environmentally unstable (such as being extremely sensitive to environmental conditions such as heating, light, and the gastrointestinal tract), which greatly limits their practical application and efficacy in eye-protecting functional foods. Anthocyanidins are hydrophilic, while lutein is hydrophobic, so it is difficult to combine the two and prepare them into the same dosage form.

[0092] Zein Nanoparticles Loaded with Lutein

[0093] In the present invention, zein and lutein are used to form nanoparticles, so that the lutein is embedded in the nanoparticles, which not only improves the light and heat stability of the lutein, but also enhances its water dispersibility, making the preparation process easier.

[0094] In particular, the nanoparticle preparation method of the present invention comprises the steps of:

[0095] (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein;

[0096] (ii) adding the alcohol solution dropwise into water, and removing the residual solvent, thereby obtaining zein nanoparticles containing lutein.

[0097] Preferably, the alcohol-water solution is obtained by mixing an ethanol-water solution of zein (such as (80±10) v / v% ethanol) and an ethanol solution of lutein.

[0098] Typically the nanoparticles are spherical in shape.

[0099] In another preferred embodiment, the ratio of lutein to zein is 1:25-120, preferably 1:50-100, such as 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110 or 1:120.

[0100] In another preferred embodiment, the dehydrated particle size of the zein nanoparticles loaded with lutein is 30-55 nm, preferably 35-50 nm.

[0101] In another preferred embodiment, the hydrated particle size of the zein nanoparticles loaded with lutein is 60-100 nm, preferably 65-85 nm.

[0102] Nanocomposite hydrogel

[0103] The nanocomposite hydrogel of the present invention uses commercially available caseinate and arabinoxylan as hydrogel matrices, which can be used to load anthocyanins, a hydrophilic component. At the same time, zein is used as a raw material to prepare nanoparticles, which can be used to load lutein, a hydrophobic component. After the two systems are blended, they are acidified and induced by a food acidifier, gluconolactone, to form a nanocomposite hydrogel that co-loads anthocyanins and lutein. The system has mild preparation conditions, can significantly improve the environmental stability (such as light and heating stability) of anthocyanins and lutein, and has the behavior of colon-targeted delivery of functional factors. The system can be used for the preparation of eye-protecting gel candies, and provides a new snack-based health care idea for alleviating visual fatigue, and has great application prospects in the field of functional foods.

[0104] Preferably, the nanocomposite hydrogel of the present invention comprises:

[0105] zein nanoparticles loaded with lutein;

[0106] anthocyanins, caseinates, arabinoxylans;

[0107] Gluconolactone; and

[0108] water.

[0109] Typically, a mixture of zein nanoparticles loaded with lutein, anthocyanins, caseinate, arabinoxylan and water is acidified with gluconolactone to form the nanocomposite. The nanocomposite hydrogel is a hydrogel in which nanoparticles are dispersed.

[0110] Preferably, the method for preparing the nanocomposite hydrogel may include the steps of:

[0111] (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein;

[0112] (ii) adding the alcohol solution dropwise into water and removing the residual alcohol to obtain or adjust the concentration to obtain an aqueous solution I of zein nanoparticles loaded with lutein;

[0113] (iii) providing an aqueous solution II comprising anthocyanidins, caseinate and arabinoxylan;

[0114] (iv) mixing the aqueous solution I with the aqueous solution II, and adding gluconolactone to form a gel, thereby obtaining the nanocomposite hydrogel.

[0115] Soft Candy

[0116] Furthermore, the present invention also provides an eye-protecting jelly candy, which comprises the nanocomposite hydrogel of the present invention as a matrix, and further comprises excipients acceptable in pharmacy or health food.

[0117] For example, another gelling agent may be added to give the soft candy the desired hardness, elasticity, cohesiveness, viscosity, chewiness, resilience and other properties, which may be adjusted as required. Preferably, the other gelling agent is selected from the group consisting of gelatin, alginate, pectin, cellulose derivatives, starch and derivatives thereof.

[0118] Furthermore, auxiliary materials such as preservatives, pigments, flavoring agents, and spices may also be included.

[0119] The soft candy of the present invention can be prepared into any shape as required, such as animals, plants or cartoon characters.

[0120] Experiments have shown that the soft candy based on the nanocomposite hydrogel of the present invention not only improves the stability of anthocyanins and lutein and enhances their delivery performance, but also has physical properties that can well meet the needs of soft candy preparation, is easy to sell and eat, and provides a new idea for snack-based health care for relieving visual fatigue.

[0121] The present invention also provides the use of the nanocomposite hydrogel or soft candy in the preparation of functional food for relieving visual fatigue. Symptoms of visual fatigue include (but are not limited to): dry eyes, astringent eyes, blurred vision, eye fatigue, etc.

[0122] The nanocomposite hydrogel or soft candy of the present invention is very suitable for various people who frequently use their eyes, such as people who rely on books or electronic screens, such as students, office workers, etc.

[0123] The main advantages of the present invention include:

[0124] The present invention constructs a nanocomposite hydrogel co-loaded with anthocyanins and lutein, realizes the simultaneous loading of hydrophilic anthocyanins and hydrophobic lutein, and significantly improves the stability and delivery effect of anthocyanins and lutein, the eye protection active ingredients, and shows colon targeted release potential in vitro, which helps to improve the bioaccessibility and bioavailability of both. The nanocomposite hydrogel of the present invention can also replace part of the gelling agent in the gel soft candy to prepare the eye protection gel soft candy, which not only plays the eye protection effect, but also enriches the nutritional composition of the soft candy.

[0125] In addition, due to the colon-targeted release performance of the nanocomposite hydrogel or the preparation of the present invention, the first-pass effect in the liver can be avoided, thereby greatly reducing the amount of active ingredients.

[0126] The present invention will be further described below in conjunction with specific implementation. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples where specific conditions are not specified are usually performed under conventional conditions, such as those described in Sambrook et al., Molecular Cloning: A Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989), or according to the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.

[0127] Example 1. Preparation of Zein Nanoparticles Loaded with Lutein, and Determination of Encapsulation and Loading Rates:

[0128] Zein (10 mg / mL) was dissolved in 80% ethanol aqueous solution (v / v) and stirred overnight. Lutein (0.5 mg / mL) was dissolved in ethanol in the dark. Then different masses of zein and lutein solutions were mixed to prepare their stock solutions (zein:Lu=100:1, 50:1, 25:1, w / w). 2 mL of zein solution or zein-Lu stock solution was added dropwise into 10 mL of deionized water and stirred at room temperature for 30 min. The residual ethanol was then dried with nitrogen to obtain zein nanoparticle system (blank NPs) or zein nanoparticle system loaded with lutein, which were named Lu-NPs-100:1, Lu-NPs-50:1, and Lu-NPs-25:1, respectively.

[0129] Take 2mL of the nanoparticle solution loaded with lutein and mix it with an equal volume of petroleum ether, vortex for 1min, centrifuge at 4500rpm for 10min, collect the organic phase, and repeat the above steps until the organic phase is colorless. Combine the organic phases and blow dry with nitrogen, then re-dissolve with 2mL of ethanol, detect lutein by HPLC, and calculate the lutein embedding rate and loading rate in the nanoparticles. The specific HPLC detection conditions are as follows: injection volume 10μL, column temperature 25℃, mobile phase methanol / 0.04M ammonium acetate (95 / 5, v / v), flow rate 1mL / min, and measure at a wavelength of 445nm. The linear equation for lutein in the range of 0.1-100μg / mL is Y=144.9x-84.09(r 2 =0.9995), and the corresponding lutein concentration was calculated according to the established standard curve. The embedding efficiency and loading capacity were calculated according to the following formulas (1) and (2).

[0130]

[0131] M u , M l , Mt They represent the mass of lutein that was not successfully loaded, the total mass of lutein added for the preparation of Lu-NPs, and the total mass of zein and lutein added, respectively.

[0132] as follows Figure 1 (a) shows the prepared zein nanoparticles (blank NPs) and zein nanoparticles loaded with lutein (Lu-NPs), from left to right, Lu-NPs-100:1, Lu-NPs-50:1, and Lu-NPs-25:1. The blank NPs solution is a clear and transparent solution, while the Lu-NPs loaded with lutein presents a yellow solution with no obvious precipitation, and the yellow color gradually deepens with the increase in the amount of lutein added. Figure 1 (b) is the Lu-NPs embedding rate and loading capacity diagram. It can be observed that with the increase of lutein addition, the embedding rate gradually decreases and the loading capacity gradually increases.

[0133] Example 2. Characterization of Nanoparticles:

[0134] 2.1 Determination of nanoparticle size and zeta potential:

[0135] The hydration diameter, polydispersity distribution index and zeta potential of blank NPs and different Lu-NPs were measured using a Malvern particle size analyzer. The experimental light source was a 4.0 mW He-Ne laser with a laser wavelength of 633 nm and a measurement angle of 90°.

[0136] The particle size and zeta potential of the nanoparticles are as follows: Figure 2 As shown, the particle size polydispersity index of all nanoparticles is below 0.3, indicating that the prepared nanoparticles have uniform particle size distribution. At the same time, it was observed that with the increase of the loading amount, the PDI gradually increased, indicating that uneven particles were produced. The particle size of blank NPs is about 66.00nm. With the increase of Lu addition, it was observed that the particle size of Lu-NPs gradually increased. The particle sizes of Lu-NPs-100:1 and Lu-NPs-50:1 were 68.71nm and 78.13nm, respectively. Lu-NPs-25:1 showed the largest particle size of about 98.76nm. In addition, the ζ potential results showed that the potentials of blank NPs and Lu-NPs were both positive. With the increase of Lu addition, the ζ potential did not change significantly ( Figure 2 (b)).

[0137] 2.2 Observation of nanoparticle microstructure:

[0138] The microscopic morphologies of freeze-dried blank NPs and Lu-NPs-100:1, Lu-NPs-50:1, and Lu-NPs-25:1 were observed using a scanning electron microscope with an acceleration voltage of 5 kV and a magnification of 200 k×.

[0139] Down Figure 3 The scanning electron microscope images and particle size distribution statistics of blank NPs and Lu-NPs are shown in the figure. It can be observed that the particle size distribution of the prepared nanoparticles is generally uniform, the particles are spherical, and the particle size distribution is between 37.51-47.95nm. Compared with the particle size measured by the Malvern particle size analyzer, the particle size is smaller. This may be because the particle size analyzer measures the hydration diameter of the nanoparticles, while the scanning electron microscope observes the dehydrated nanoparticles, which makes the corresponding measured particle size results different. However, the particle size increase trend of the nanoparticles measured by the scanning electron microscope and the particle size analyzer method is consistent. With the addition of Lu, the particle size of the nanoparticles gradually increases. In addition, with the increase in the amount of Lu added, some irregularly shaped particles can be observed. When the mass ratio of zein to Lu is 25:1, the irregularly shaped particles appear most obviously, which may be related to its relatively low encapsulation rate.

[0140] 2.3 Fluorescence spectrum:

[0141] The intrinsic fluorescence of blank NPs and Lu-NPs-100:1, Lu-NPs-50:1, and Lu-NPs-25:1 was scanned at 298, 303, and 313 K using a multifunctional microplate reader. The excitation wavelength was set to 280 nm, and the emission wavelength was set to 300 to 500 nm. In addition, the relevant thermodynamic parameters (Equations (3)-(5)) were further calculated using the double logarithmic equation and the van der Hoff equation to study the interaction between lutein and zein.

[0142] F0 / F=1+K sv [β]=1+k q τ0[β] (3)

[0143] log((F0-F) / F)=logK a +nlog[Q] (4)

[0144] LqCy a =-ΔH / RT+ΔS / R (5)

[0145] ΔG=ΔH-TΔS (6)

[0146] Down Figure 4(a)(b)(c) are the fluorescence spectra of different nanoparticles at 298, 303 and 313 K, respectively. BlankNPs were observed to show the maximum fluorescence emission peak at 312 nm, which is because zein contains a higher amount of tyrosine residues. With the addition of lutein, the maximum fluorescence emission peak position of zein nanoparticles at 312 nm did not move, but the fluorescence intensity decreased significantly, indicating that the emission spectrum of zein decreased with the increase in the amount of Lu added, and fluorescence quenching occurred.

[0147] Fluorescence quenching can be divided into dynamic quenching, static quenching or both. According to the Stern-Volmer equation, k q Values ​​higher than 2×10 10 M -1 s -1 The quenching is caused by the formation of the ground state complex. On the contrary, less than 2×10 10 M -1 s -1 The value of means that the quenching intensity reduction is caused by collision. The calculated K SV Value, k q The values ​​are summarized in Table 1. K SV They are 0.568×10 5 M -1 , 0.592×10 5 M -1 , 0.620×10 5 M -1 , k q 0.568×10 13 M -1 s -1 , 0.592×10 13 M - 1 s -1 , 0.620×10 13 M -1 s -1 Much larger than 2×10 10 M -1 s -1 The results show that the quenching process between zein and lutein is mainly static quenching caused by complex formation. The binding constant K is further calculated. a and binding site n, and the related parameters are summarized in Table 1. n is approximately 1, indicating that there is a single binding site in their mixture, and the affinity is the highest at 313K (1.035×10 7 M -1). Several thermodynamic parameters, including ΔH, ΔS, and ΔG, were calculated based on the fluorescence spectrum to further determine the molecular interaction mode between Lu and the zein nanoparticle carrier. The results showed that the values ​​of ΔH and ΔS were 24.443 kJ / mol and 212.672 J / mol / K, respectively, and the values ​​of ΔG were negative at 298, 303, and 313 K, indicating that lutein and zein bind spontaneously. According to the theory of Ross and Olsson, when ΔH>0 and ΔS>0, hydrophobic interactions dominate the binding reaction.

[0148] Table 1 Calculation results of thermodynamic parameters

[0149]

[0150] 2.4 Infrared spectroscopy (FTIR):

[0151] Lutein, zein, zein nanoparticles, physical mixtures of lutein and zein nanoparticles, and zein nanoparticles loaded with different amounts of lutein were scanned using infrared spectroscopy in the range of 400–4000 cm -1 , resolution 2cm -1 , further analyzed the interaction between lutein and zein.

[0152] Down Figure 5 In the infrared spectrum of lutein, 2952 cm -1 The peak at 2916 cm represents OH stretching vibration. -1 , 2851cm -1 The peak at 1360 cm represents CH stretching vibration. -1 , 1022cm -1 and 962cm -1 The peaks at 1644 cm in the infrared spectrum of zein represent the out-of-plane deformation of -CH=CH-, the in-plane bending vibration of -CH and the dimethyl splitting. -1 With 1534cm -1 The protein-characteristic amide I band (representing CN and CO stretching) and amide II band (CN stretching and NH bending), 3283 cm -1 The peak at represents the stretching vibration of the -OH group in zein. After physically mixing zein nanoparticles with lutein, the characteristic peaks of the two substances can be observed to appear simultaneously in the infrared spectrum of the mixture. However, the characteristic peaks related to lutein in the infrared spectrum of the lutein-loaded nanoparticles disappeared, and only the protein characteristic peaks appeared. In addition, compared with the peak of the amide band of zein, the amide band in the Lu-NPs spectrum was red-shifted, with the peak positions at 1538cm and 1547cm, respectively.-1 With 1650cm -1 , indicating that there is a hydrophobic interaction between zein and lutein. In addition, the -OH peak position in Lu-NPs also moved to 3291 cm -1 , which indicates that there are hydrogen bonding interactions during the formation of Lu-NPs. The above results indicate that there are hydrophobic and hydrogen bonding interactions during the formation of zein nanoparticles loaded with lutein.

[0153] 2.5X-ray diffraction:

[0154] Lutein, zein, a physical mixture of lutein and zein nanoparticles, and zein nanoparticles loaded with lutein were scanned using a multifunctional X-ray diffractometer with a Cu target, a voltage of 40 kV, a current of 40 mA, and a scanning range of 5-55°.

[0155] The XRD spectrum is as follows Figure 6 As shown. The spectrum of zein nanoparticles shows two humps at 8.9° and 19.4°, indicating that the protein exists in an amorphous state. The lutein spectrum shows multiple obvious diffraction peaks between 5-27°, indicating that lutein mainly exists in crystalline form. In the spectrum of the physical mixture of lutein and zein nanoparticles, although the intensity of the characteristic crystal peak of lutein has decreased, it shows a peak consistent with that of lutein powder. The spectrum of the nanoparticles loaded with lutein has changed significantly, and all the crystal peaks of lutein have disappeared, indicating that lutein is distributed in the nanoparticles in an amorphous state after being embedded in the nanoparticles. It also shows that lutein is not adsorbed on the surface of the nanoparticles, but is wrapped inside the nanoparticles to achieve loading. In addition, combining the results of infrared, X-ray diffraction and fluorescence interaction, it can be seen that lutein and zein are mainly loaded through hydrophobic interactions and hydrogen bonding interactions. Lutein reduces its crystallinity by transforming into an amorphous state, and the water dispersibility of lutein is enhanced in the process.

[0156] Example 3. Preparation of nanocomposite hydrogel loaded with anthocyanins and lutein:

[0157] A certain amount of anthocyanin, casein and arabinoxylan were added to deionized water and stirred overnight at room temperature in the dark. The concentration of casein (Cas) was 60 mg / mL, the concentration of arabinoxylan (AX) was 12 mg / mL, and the amount of anthocyanin (ACN) added was 0.4 g / g·Cas. Zein (10 mg / mL) was dissolved in 80% ethanol aqueous solution (v / v) and stirred overnight. Lutein (0.5 mg / mL) was dissolved in ethanol in the dark, and then a certain volume of lutein solution was blended with zein solution (zein: lutein = 50:1, w / w). Take 2 mL of the above mixture and add it dropwise to 10 mL of deionized water at a constant speed. Stir magnetically at room temperature for 30 minutes, and then blow off the residual ethanol with nitrogen. Then, the zein nanoparticle solution loaded with lutein (about 1.34 mg / mL) was mixed with the composite hydrogel solution loaded with anthocyanin at 10%, 20%, and 40% (v / v) for 30 minutes, and then gluconolactone (GDL, 0.1 g / g·Cas) was added and stirred thoroughly. After GDL was dissolved evenly, stirring was stopped. After standing at 30°C for 4 hours to gel, nanocomposite hydrogels loaded with anthocyanin and lutein were prepared and named 10% Lu-NPs / ACN-gel, 20% Lu-NPs / ACN-gel, and 40% Lu-NPs / ACN-gel, respectively. The hydrogel loaded with anthocyanin without adding nanoparticles (ACN-gel) was used as a control.

[0158] like Figure 7 The digital photo of the prepared nanocomposite hydrogel co-loaded with anthocyanin and lutein is shown. It can be observed that the samples are all purple. It is also observed that compared with the composite hydrogel loaded with anthocyanin only, the nanocomposite hydrogel formed by adding 10% Lu-NPs and 20% Lu-NPs is basically the same as ACN-gel, and has no obvious effect or damage on the hydrogel structure. After demolding, the intact structure and smooth surface are still maintained. However, when the amount of Lu-NPs added is increased to 40%, the structure of the nanocomposite hydrogel is significantly affected, the structure becomes soft and broken, and the original structural integrity cannot be maintained after demolding.

[0159] Example 4. Characterization of Nanocomposite Hydrogels:

[0160] 4.1 Microscopic morphology observation:

[0161] The prepared nanocomposite gel was freeze-dried, and the sample was sprayed with gold to give it conductivity. The internal microstructure of the nanocomposite gel was observed using a scanning electron microscope. The acceleration voltage of the scanning electron microscope was 5kV and the magnification was 400 times. In addition, the three-dimensional structure of the hydrogel was observed using an X-ray microscope. During the test, the acceleration voltage was 80kV and the power was 7W. During the scanning process, the sample was rotated 360° around the vertical axis. The voxel resolution collected was 1μm, and the 3D reconstruction was performed using the DRAGONFLY software.

[0162] like Figure 8 (a) As shown in the scanning electron microscope micrograph, ACN-gel has an interconnected porous network structure with uniform pore distribution. After adding 10% or 20% Lu-NPs, the structure of 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel did not change significantly. However, 40% Lu-NPs / ACN-gel showed a loose gel network structure with large and irregularly distributed pores.

[0163] at the same time, Figure 8 (b) shows the X-ray image of the three-dimensional structure of the gel sample before and after the addition of Lu-NPs. In X-ray microscopy imaging, the larger the atomic mass and the higher the density, the brighter the image. The results show that ACN-gel has more bright green areas, and the dense three-dimensional network structure and relatively uniform pore distribution can be clearly seen. In addition, the network structure was observed to be somewhat loose in 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel, but the overall network structure was consistent with ACN-gel. As the amount of Lu-NPs added increased to 40%, the nanocomposite hydrogel showed a significantly loose and uneven network structure. In addition, X-ray microscopy can also provide information on the porosity of the gel sample. According to calculations, the porosities of ACN-gel, 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel are relatively close, at 23.96%, 27.32% and 31.11%, respectively. The porosity of 40% Lu-NPs / ACN-gel increased significantly to 48.48%, indicating that excessive addition of Lu-NPs would affect the maintenance of the dense network structure in the gel.

[0164] 4.2 Infrared spectroscopy analysis (FTIR):

[0165] The infrared spectra of ACN-gel and Lu-NPs / ACN-gel are shown in Fig. 9 In the spectrum of ACN-gel, we can see that -1 The characteristic bending vibration of CH in the aromatic ring of ACN was observed at 1077 cm -1 and 1150cm-1 The peaks that appear represent the CO stretching vibration and COC stretching vibration in ACN. In addition, 1524 cm -1 、1630cm -1 and 3269cm -1 The peak at 1530 cm represents the stretching vibration of amide I and amide II bands and -OH of casein in ACN-gel. -1 The amide II band at 40% Lu-NPs / ACN-gel was slightly red-shifted, which may be due to the hydrophobic effect involved in the formation of nanocomposite hydrogels. In addition, with the increase of Lu-NPs addition, the hydroxyl peak of 10% Lu-NPs / ACN-gel, 20% Lu-NPs / ACN-gel and 40% Lu-NPs / ACN-gel increased from 3269 cm -1 Move to 3272cm -1 、3275cm -1 and 3278cm -1 , indicating that there is a hydrogen bonding interaction between Lu-NPs and the gel matrix. 4.3 Rheological properties:

[0166] The change of gel strength before and after adding Lu-NPs was analyzed by rheological analysis. Fig.10 As shown in (a), the apparent viscosity of the gel sample decreases with the increase of shear rate, showing shear thinning behavior and is a non-Newtonian fluid. -1 Within the shear range, the apparent viscosity values ​​of ACN-gel, 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel are very close, while the apparent viscosity of 40% Lu-NPs / ACN-gel decreases significantly. Fig.10 (b) shows that the G' values ​​of all gel samples are higher than their G" values, indicating the formation of an elastic gel structure. It was also observed that there was no significant difference in the G' and G" values ​​of 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel compared with ACN-gel. However, the G value of 40% Lu-NPs / ACN-gel decreased significantly. Therefore, the decrease in the apparent viscosity and G value of 40% Lu-NPs / ACN-gel further indicates the weakening of its gel strength.

[0167] Example 5. Stability study of anthocyanins and lutein:

[0168] The temperature stability and light stability of free anthocyanin (free ACN), free lutein (free Lu), lutein-loaded nanoparticle solution (Lu-NPs), and anthocyanin and lutein loaded in nanocomposite hydrogel were tested. The samples were sampled at 0, 1, 2, and 4 days in a light box with a white light illumination of 6500 Lux, ultraviolet 130 uW, and 25 ° C, and the light stability test was performed. In addition, the samples were heated in a water bath at 80 ° C, and samples were taken at 0, 2, 4, and 8 hours, respectively, and the thermal stability test was performed on the samples. 1 mL of distilled water was added to the hydrogel sample for grinding, and then 5 mL of ethanol was added and mixed and vortexed for 1 minute. The sample was then ultrasonicated for 30 minutes and centrifuged at 4500 rpm for 10 minutes. The supernatant was taken to determine the residual content of anthocyanin and lutein in the hydrogel sample. 1 mL of lutein-loaded nanoparticles was added to 4 mL of ethanol, mixed and vortexed for 1 min, and then the sample was ultrasonicated for 30 min and centrifuged at 4500 rpm for 10 min to extract the remaining lutein in the nanoparticles for residual content detection.

[0169] The anthocyanin content was determined using the HPLC method. The specific test conditions are as follows: injection volume of 20 μL, mobile phase A (1% formic acid water), mobile phase B (1% formic acid acetonitrile), flow rate of 0.8 mL / min, column temperature of 30 ° C. Elution gradient: 0 min A phase / B phase (92:8, V / V), 2 min A phase / B phase (88:12, V / V), 5 min A phase / B phase (82:18, V / V), 10 min A phase / B phase (80:20, V / V), 12 min A phase / B phase (75:25, V / V), 14 min A phase / B phase (92:8, V / V), 20 min A phase / B phase (92:8, V / V), measured at a wavelength of 520 nm, and the linear equation for anthocyanin in the range of 0.1-12 mg / mL was Y=66.28x+2.039 (r 2 =0.9998), and the corresponding anthocyanin concentration was calculated according to the established standard curve. The lutein determination method was the same as the method for lutein embedding rate detection. The retention rate of anthocyanin or lutein was calculated using the following formula (6). At the same time, the retention rates of anthocyanin and lutein were further fitted using the first-order degradation kinetics.

[0170]

[0171] ln(C t / C0)=kt (8)

[0172] t 1 / 2 =-ln0.5×k -1 (9)

[0173] Among them Ct is the content of anthocyanin or lutein in the sample at the set corresponding time point, C0 is the initial content of anthocyanin or lutein in the sample, k, t 1 / 2 are the reaction rate constant and half-life of degradation, respectively.

[0174] like Fig.11 As shown in (a), the retention rate of free anthocyanins decreased significantly with the extension of illumination time. After 1, 2 and 4 days of illumination, the retention rates of free anthocyanins were only 71.49%, 47.12% and 19.72%, respectively. Compared with free anthocyanins, the photostability of anthocyanins loaded in ACN-gel or Lu-NPs / ACN-gel was significantly enhanced. Using the first-order degradation kinetics (R 2 The protective effect of the gel on ACN was further studied. As shown in Table 1, the degradation rate constant (K) of free ACN was 0.4105d -1 , half-life (t 1 / 2 ) was 1.6885 d, while the t of ACN loaded in ACN-gel, 10% Lu-NPs / ACN-gel, 20% Lu-NPs / ACN-gel and 40% Lu-NPs / ACN-gel was 1 / 2 The lengths of the photostability of ACN were extended by 4.59, 4.23, 4.31, and 4.04 times, respectively. This shows that ACN-gel and nanocomposite hydrogels have similar protective effects on the photostability of ACN and are not significantly affected by the amount of Lu-NPs added. In addition, in the thermal stability test, the gel sample also has a similar protective effect on anthocyanins. Fig.11 (b) After heating at 80℃ for 8h, only 22.75% of free anthocyanins remained, and its K value and t 1 / 2 The values ​​are 0.1817h -1 In contrast, anthocyanins loaded in ACN-gel and Lu-NPs / ACN-gel showed smaller K values ​​and longer t 1 / 2 Value (Table 2). This indicates that the network structure of the gel plays an important role in hindering the penetration of light and heat, thereby reducing the structural changes of anthocyanins in the gel system. In addition, anthocyanins can bind to casein through non-covalent interactions to form anthocyanin-casein complexes, thereby reducing the effects of light and heat on anthocyanins and further improving the stability of anthocyanins.

[0175] Fig.11(c) It can be observed that the retention rates of free lutein after 1, 2 and 4 days of illumination were 59.62%, 36.02% and 13.89%, respectively. When lutein was encapsulated in zein nanoparticles, its photostability was enhanced, and the retention rate increased to 42.88% after 4 days of illumination. At the same time, the K value also increased from 0.4935d- 1 Down to 0.2141d -1 , t 1 / 2 The value was extended from 1.4046d to 3.2375d (Table 2). In addition, compared with Lu-NPs, Lu-NPs / ACN-gel has a better protective effect on lutein. After 4 days of illumination, the retention rate of Lu-NPs / ACN-gel exceeded 72%. Fig.11 It was also observed in (d) that the thermal stability of Lu-NPs and Lu-NPs / ACN-gel was similarly improved compared with free lutein. After 8 h of thermal treatment, the retention rates of free lutein and Lu-NPs were 27.88% and 33.57%, respectively, while the retention rates of Lu-NPs / ACN-gel ranged from 59.22% to 63.55%. In addition, the t 1 / 2 The value more clearly reflects the improvement of lutein thermal stability, which is different from the t 1 / 2 Compared with the value (4.4150h), the t values ​​of Lu-NPs, 10% Lu-NPs / ACN-gel, 20% Lu-NPs / ACN-gel and 40% Lu-NPs / ACN-gel were 1 / 2 The values ​​were 5.0521, 12.6996, 11.6908 and 10.7498 h, respectively. In summary, the addition of Lu-NPs to ACN-gel can further improve the stability of lutein, which may be due to the three-dimensional network structure of the hydrogel providing another solid barrier for lutein in addition to zein encapsulation, reducing the effects of light and heat treatment on lutein.

[0176] Table 2 First-order degradation kinetics of anthocyanins or lutein under photothermal treatment

[0177]

[0178] Example 6. In vitro release behavior:

[0179] The nanocomposite hydrogel samples with known anthocyanin and lutein loading were transferred to 10 mL of simulated gastric fluid (SGF, pH = 2, pepsin concentration 3.2 mg / mL), and placed in a constant temperature oscillator at 37 ° C, 120 rpm to simulate the in vitro release of the gastric environment. After 2 hours, 10 mL of simulated intestinal fluid (SIF, pH = 6.8, trypsin 200 U / mL) was added to simulate small intestinal digestion for 4 hours. Finally, the pH of the digestive fluid was adjusted to 7.4 and xylanase solution (2.4 U / mg AX) was added to simulate colon digestion (SCF, pH 7.4) for 18 hours. In addition, Tween 80 (1%, v / v) was additionally added to the digestive fluid to meet the lutein sink condition. During the experiment, 1 mL of digestion solution was taken at 0.25, 0.5, 1, 2, 3, 4, 6, 8, 10, 12, 16, and 24 h, and an equal volume of digestion solution was added. The digestion solution was centrifuged at 12000 rpm for 10 min, and the release of anthocyanins and lutein in the supernatant was analyzed by the HPLC method mentioned above. The cumulative release rate (%) of anthocyanins and lutein was calculated using the following formula, and the cumulative release curve of anthocyanins and lutein was drawn. In addition, the release kinetics of the samples were fitted using the Ritger-Peppas model to further reflect the release characteristics of anthocyanins and lutein in different samples.

[0180]

[0181] C t and C0 are the anthocyanin content in the digestive fluid at the sampling time and the original anthocyanin content in the sample, respectively, a is the release rate constant, and n is the exponent.

[0182] Fig.12(a) is the in vitro release curve of ACN-gel, Lu-NPs and Lu-NPs / ACN-gel. The results show that ACN-gel can significantly slow down the release of anthocyanins in simulated gastric juice and simulated small intestinal juice, which may be related to the arabinoxylan component in ACN-gel. Arabinoxylan has the properties of dietary fiber and can effectively help ACN-gel resist digestion by pepsin and trypsin. At the same time, it can be observed that the addition of 10% and 20% Lu-NPs to the gel system did not change the release curve of anthocyanins. The release curves of ACN-gel, 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel almost overlap. At the same time, the release rate of anthocyanins in 40% Lu-NPs / ACN-gel was significantly faster, regardless of the simulated gastric, small intestinal or colonic digestion stage. About 46.99% and 67.23% of anthocyanins have been released in the simulated gastric digestion and simulated small intestinal stages. The in vitro release data were used to further elucidate the basic mechanism of anthocyanin release using the Ritger-Peppas model. As shown in Table 3, the anthocyanin release curves of ACN-gel and the three nanocomposite hydrogels had a high degree of fit with the Ritger-Peppas model (R 2 >0.96), the calculated release index (n) was between 0.3289 and 0.4234, and when n was less than 0.45, it indicated diffusion-controlled release.

[0183] like Fig.12As shown in (b), the cumulative release of lutein in Lu-NPs in the gastrointestinal stage was about 75.89%, of which the rapid release of lutein was mainly due to the easy degradation of zein by gastrointestinal digestive enzymes, resulting in the disintegration of Lu-NPs and the rapid release of loaded lutein. In contrast, the cumulative release rate of lutein in 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel was significantly slowed down, with the release rates in the simulated gastric digestion and simulated small intestinal digestion stages being only 15.67%-17.59% and 39.26%-41.72%. The slow release of lutein may be due to the fact that Lu-NPs were trapped in the gel network, and the matrix of the gel network contained arabinoxylan, which was resistant to gastrointestinal enzyme digestion. It greatly delayed the contact and degradation of the nanoparticles with the gastrointestinal digestive enzymes, thereby slowing down the release of lutein. In the subsequent simulated colonic digestion stage, the remaining lutein (about 50%) was observed to be released rapidly. Because the introduction of xylanase in the simulated colon digestion stage can depolymerize the xylose skeleton of arabinoxylan and destroy the gel structure, so that Lu-NPs are exposed to the release medium and the loaded lutein is quickly released. At the same time, the lutein release rate of 40% Lu-NPs / ACN-gel in the simulated gastric and small intestinal digestion stages is significantly higher, with about 61.17% of lutein released. However, its release rate is still slower than that of Lu-NPs. In addition, the characteristic release index (n) of Lu-NPs, 10% Lu-NPs / ACN-gel, 20% Lu-NPs / ACN-gel and 40% Lu-NPs / ACN-gel was further analyzed, which were 0.3151, 0.5831, 0.5552 and 0.4243, respectively. The release index of Lu-NPs is less than 0.45, so diffusion is the main release mechanism of lutein in Lu-NPs. The release index values ​​of 10% Lu-NPs / ACN-gel and 20% Lu-NPs / ACN-gel were between 0.45 and 0.89, so both diffusion-controlled release and swelling-controlled release were involved in the release of lutein. However, the excessive addition of Lu-NPs (40%) significantly increased the pore size of the nanocomposite hydrogel and the porosity of the gel structure, so the release of lutein in 40% Lu-NPs / ACN-gel returned to being controlled only by diffusion.

[0184] Table 3 Fitting parameters of the Ritger-Peppas model in in vitro release curves

[0185]

[0186] Example 7. Preparation of simulated gel candy:

[0187] Based on the above research results, 20% Lu-NPs / ACN-gel was selected as a nanocomposite hydrogel co-loaded with anthocyanins and lutein as a component for preparing gel candy gel. A certain mass of anthocyanins, casein and arabinoxylan were added to deionized water and stirred overnight at room temperature in the dark. The concentration of casein (Cas) was 60 mg / mL, the concentration of arabinoxylan (AX) was 12 mg / mL, and the amount of anthocyanin (ACN) added was 0.4 g / g·Cas. Zein (10 mg / mL) was dissolved in 80% ethanol aqueous solution (v / v), stirred overnight, and lutein (0.5 mg / mL) was dissolved in ethanol in the dark, and then a certain volume of lutein solution was blended with zein solution (zein: lutein = 50:1, w / w). Take 2mL of the above mixture and add it dropwise to 10mL of deionized water at a constant speed, stir magnetically at room temperature for 30min, and then blow off the residual ethanol with nitrogen. Then, mix the zein nanoparticle solution loaded with lutein and the composite hydrogel solution loaded with anthocyanin at 10%, 20%, and 40% (v / v) for 30min, and then add 1%, 2%, 5%, 10%, and 15% (w / v) of gelatin, a gelling agent commonly used in commercial soft candies, to the nanocomposite hydrogel, respectively, and stir at 45°C for 1h to fully dissolve. Finally, gluconolactone (GDL, 0.1 g / g·Cas) was added and stirred thoroughly. Stirring was stopped after GDL was evenly dissolved. After standing at 30°C for 4 hours to gel, a gel candy with co-loaded anthocyanins and lutein was prepared and named Lu-NPs / ACN-gel-1%G, Lu-NPs / ACN-gel-2%G, Lu-NPs / ACN-gel-5%G, Lu-NPs / ACN-gel-10%G, and Lu-NPs / ACN-gel-15%G. At the same time, a nanocomposite hydrogel (Lu-NPs / ACN-gel) without gelatin was used as a control. Fig.13 (a) is a digital photo of the gel sample prepared after adding gelatin. It is observed that with the addition of gelatin, the gelation rate of the sample is significantly accelerated, the surface of the formed gel sample is drier, the structure is complete after demolding, the structure does not change after long-term storage, and the gel strength is greater. Fig.13 (b) is a photo of the effect of a jelly candy with 10% gelatin added, which has a visual effect similar to candies sold on the market.

[0188] Example 8. Texture test:

[0189] To further verify the comparability of the prepared gel candy with commercially available gel candies, four types of snack candies sold on the market were used as references (brands were Beijing Tong Ren Tang (Tong), Swisse (Swisse), Nature's way Australia Cuiwei (Nature) and Black Forset Fruity Forest (Forest)). The physical properties (hardness, elasticity, cohesion, viscosity, chewiness, and resilience) of the commercially available gel candies and the simulated gel candies prepared in the laboratory were tested and compared using a texture analyzer. During the test, each piece of gel candy was cut into small rectangular blocks of the same shape and size, and each group of samples was measured 4 times in parallel. The measurement parameters of the texture analyzer were: using a P / 50 cylindrical probe, the speed before the test was 1mm / s, the test speed was 1mm / s, the speed after the test was 1mm / s, the deformation was 50%, the trigger force was 5g, and the dwell time was 5s.

[0190] The texture test results are shown in Table 4 below. When the gelatin addition is 5% or more, the texture results can be similar to those of commercially available gels. This shows that the prepared nanocomposite hydrogel is used as a component of the gelling agent in gel candies and integrated into the formula of gel candies. It is feasible to develop into a commercially available gel soft candy product. The addition of dietary fiber polysaccharides and high-quality protein can enrich the nutritional composition of gel soft candies, while achieving the simultaneous loading of lutein and anthocyanins, supplementing the eye protection active ingredients, and is expected to develop into a soft candy product with both taste and functional characteristics.

[0191] Table 4 Texture test results of four commercially available jelly candies and nanocomposite hydrogels with gelatin added

[0192]

[0193]

[0194] discuss

[0195] In recent years, dietary supplements on the market have begun to innovate, breaking the traditional capsule and tablet forms, and pursuing diversification in dosage forms and packaging. Dietary nutrients in the form of soft candies, jellies, dairy products, beverages, etc. continue to emerge. Supplementing healthy active ingredients in the form of snacks will be a major development trend of dietary supplements in the future. At present, the popular eye protection ingredients in eye protection foods on the market mainly include lutein, zeaxanthin, blueberries, bilberries, and vitamins and minerals. Anthocyanins and lutein are two natural bioactive compounds and are dietary supplements that are beneficial to eye health. However, due to the environmental instability and different physical and chemical properties of anthocyanins and lutein, simply compounding anthocyanins and lutein may greatly limit their synergistic efficacy and bioavailability. Therefore, it is expected to design a delivery system with excellent properties for simultaneous encapsulation, protection, and delivery of these two bioactive compounds, anthocyanins and lutein, and a novel form of snacks.

[0196] Hydrogel is a hydrophilic polymer material with a three-dimensional network structure. It has adjustable mechanical properties, biocompatibility, environmental stability and other characteristics. Its unique texture characteristics give it the potential to develop into a snack-like dietary supplement. By adjusting the type, composition, and ratio of hydrogel raw materials, innovative product dosage forms with a similar taste to soft candies can be prepared. In addition, hydrogels prepared with natural polymers as raw materials have many characteristics such as edibility, combinable nutrients, and good biocompatibility. However, the hydrophilic nature of hydrogels makes them more suitable for the delivery of hydrophilic components. In recent years, nanocomposite hydrogels have received increasing attention as a new delivery system. They are prepared by introducing nanomaterials (such as nanoparticles) into the hydrogel network. Nanocomposite hydrogels can combine the advantages of both hydrogel and nanoparticle systems, making them have greater application potential in the field of bioactive ingredient delivery. For example, the addition of nanoparticles can improve the mechanical properties of hydrogels; the porous structure of hydrogels can load and disperse nanoparticles, effectively reducing the aggregation of nanoparticles, and hydrogels can also serve as a physical barrier to resist adverse external environments and protect nanoparticles.

[0197] The inventors found in their research that arabinoxylan / casein composite hydrogel is an excellent hydrogel carrier with a dense network structure, strong gel strength and hydrophilic component loading delivery potential. However, the research on nanocomposite hydrogels based on arabinoxylan / casein hydrogels is still very limited. Zein is a food-grade natural polymer extracted from corn. There are a large number of hydrophobic amino acids in zein, and the hydrophilic amino acid region and the hydrophobic amino acid region have obvious partitions, which gives it unique self-assembly properties. It can spontaneously assemble into nanoparticles in water and can effectively encapsulate hydrophobic active ingredients.

[0198] Due to the instability, low bioavailability, different hydrophilicity and hydrophobicity of anthocyanins and lutein, as well as the potential benefits for eye protection, in this study, lutein was encapsulated by zein nanoparticles and anthocyanins were loaded by arabinoxylan / casein composite hydrogels, and nanocomposite hydrogels were prepared by combining the two. First, the effects of different nanoparticle addition amounts on the formation, microstructure and properties of the prepared nanocomposite hydrogels were studied. At the same time, the performance of the dual-component loaded nanocomposite hydrogels in protecting and delivering anthocyanins and lutein was studied, aiming to provide a feasible method for improving the stability and bioavailability of anthocyanins and lutein, and at the same time provide a new idea for the development of functional gel candies that are both healthy and have a soft candy taste.

[0199] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A nanocomposite hydrogel, characterized in that: include: zein nanoparticles loaded with lutein; anthocyanins, caseinates, arabinoxylans; Gluconolactone; and water.

2. The nanocomposite hydrogel according to claim 1, characterized in that include: 0.05-1 parts by weight, preferably 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or 0.8 parts by weight of zein nanoparticles loaded with lutein; 15-30 parts by weight of anthocyanins, preferably 16, 18, 20, 22, 24, 26 or 28 parts by weight; 40-70 parts by weight of casein, preferably 45, 50, 55, 60, 65 or 68 parts by weight; 5-20 parts by weight of arabinoxylan, preferably 8, 10, 12 or 15 parts by weight; 2-8 parts by weight, preferably 4, 5, 6 or 7 parts by weight of gluconolactone; and Water: 700-950 parts by weight, preferably 800, 850, 880, 900, 920 or 940 parts by weight.

3. The nanocomposite hydrogel according to claim 2, characterized in that The nanocomposite hydrogel comprises 0.001-0.02 parts by weight of lutein, preferably 0.002, 0.004, 0.006, 0.008, 0.01, 0.012, 0.015 or 0.018 parts by weight.

4. The nanocomposite hydrogel according to claim 1, characterized in that include: Zein nanoparticles loaded with lutein 0.05-1 g / L, preferably 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or 0.8 g / L; Anthocyanins 15-30 g / L, preferably 16, 18, 20, 22, 24, 26 or 28 g / L; Casein 40-70 g / L, preferably 45, 50, 55, 60, 65 or 68 g / L; Arabinoxylan 5-20 g / L, preferably 8, 10, 12 or 15 g / L; and Gluconolactone 2-8 g / L, preferably 4, 5, 6 or 7 g / L.

5. The nanocomposite hydrogel according to claim 1, characterized in that The weight ratio of lutein to zein is 1:25-120, preferably 1:50-100, such as 1:40, 1:50, 1:55, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110 or 1:

120.

6. The method for preparing the nanocomposite hydrogel according to claim 1, characterized in that: Includes steps: (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein; (ii) adding the alcohol solution dropwise into water and removing the residual alcohol to obtain or adjust the concentration to obtain an aqueous solution I of zein nanoparticles loaded with lutein; (iii) providing an aqueous solution II comprising anthocyanidins, caseinate and arabinoxylan; (iv) mixing the aqueous solution I with the aqueous solution II, and adding gluconolactone to form a gel, thereby obtaining the nanocomposite hydrogel.

7. A soft candy, characterized in that: include: zein nanoparticles loaded with lutein; anthocyanins, caseinates, arabinoxylans; Additional gelling agents; Gluconolactone; and water.

8. The soft candy according to claim 7, characterized in that The additional gelling agent is selected from the group consisting of gelatin, alginates, pectin, cellulose derivatives, starch and derivatives thereof.

9. The method for preparing soft candy according to claim 3, characterized in that: Includes steps: (i) providing an alcohol-water solution (e.g., 80-90 v / v% alcohol) containing lutein and zein; (ii) adding the alcohol solution dropwise into water and removing the residual alcohol to obtain or adjust the concentration to obtain an aqueous solution I of zein nanoparticles loaded with lutein; (iii) providing an aqueous solution II-a comprising anthocyanidins, caseinate, arabinoxylan and the additional gelling agent; (iv) mixing the aqueous solution I with the aqueous solution II-a, and adding gluconolactone to form a gel, thereby obtaining the soft candy.

10. Use of the nanocomposite hydrogel according to claim 1 or the soft candy according to claim 3 in preparing functional food for relieving visual fatigue.

Citation Information

Cited By

  • Preparation method of interpenetrating cross-linked network emulsion gel for improving stability of anthocyanin and xanthophyll

    CN121220699A